Private Self-Consciousness and Self-Compassion as Predictors of Coping Styles: Mediating Role of Emotional Intelligence and Resilience - Mann, Chahat (My University, 2022)
The study aimed to investigate the mediating role of Emotional Intelligence and Resilience in the relationship between Private Self-Consciousness and Coping Styles and in the relationship between Self-Compassion and Coping Styles. The study was conducted using the SelfReflection and Insight Scale as a measure of private self-consciousness, the Self-Compassion Scale-Short Form as a measure of Self-Compassion, the TEIQue-SF as a measure of emotional intelligence, the 10-item Connor-Davidson Resilience Scale as a measure of resilience and the Brief Cope Scale to measure of coping styles. Data analysed from 200 participants found Private Self-Consciousness to be positively correlated to Emotional Intelligence, Resilience, Adaptive Coping Styles and negatively correlated to Maladaptive Coping Styles; SelfCompassion to be positively correlated to EmotionalIntelligence, Resilience, Adaptive Coping Styles and negatively correlated to Maladaptive Coping Styles. Emotional Intelligence was found to be positively correlated to Adaptive Coping Styles and negatively correlated to Maladaptive Coping Styles; Resilience was found to be positively correlated to Adaptive Coping Styles and negatively correlated to Maladaptive Coping Styles. Partial Least Squares analysis found that EmotionalIntelligence fully mediates the relationship between Private SelfConsciousness and Maladaptive Coping Styles and the relationship between Self-Compassion and Maladaptive Coping Styles whereas Resilience fully mediates the relationship between Self-Compassion and Adaptive Coping Styles, the relationship between Self-Compassion and Maladaptive Coping Styles and the relationship between Private Self-Consciousness and Adaptive Coping Styles. However, the model fit analysis found that the overall mediation model was not significant.
Keywords: Private Self-Consciousness; Self-Compassion; Emotional Intelligence; Resilience; Adaptive Coping Styles; Maladaptive Coping Styles